Mini makers : crafty makes to create with your kids - Minter, Laura; Williams, Tia, 1982- (Guild of Master Craftsman Publications Ltd., 2016)
You don't need to be an expert crafter to make things with children. Minter and Williams provide ideas that will have you painting, cutting, sewing and baking. You'll be creating imaginative play while developing fine motor control and promoting life skills.